Intraspecific variation in the functional responses of an invasive tropical freshwater fish under increasing temperature regimes - Matteo Ventura; Simone Cittadino; Edoardo Calizza; Giulio Careddu; Simona Sporta Caputi; Loreto Rossi; Maria Letizia Costantini (Scientific Reports, 2024)
Abstract Global warming and the introduction of non-native fish represent major threats to freshwater biodiversity worldwide, but their effects have usually been investigated separately. Since most fish are ectotherms, their metabolism and feeding behaviour are highly influenced by temperature. Increasing water temperatures may thus exacerbate the impact of non-native fish, particularly those adapted to warmer conditions, on prey populations. Increasing temperature can also result in divergences between the impacts of females and males, especially in sexually dimorphic species. The globally invasive tropical guppy Poecilia reticulata Peters, a popular aquarium fish also used for control of mosquito-borne diseases and as a model species in ecological and evolutionary studies, exhibits strong sexual dimorphism and larvivory. This laboratory study examined prey consumption and prey size selection by guppies fed with chironomid larvae under varying temperature conditions. The effect of sex, pregnancy and prey body size on the guppy’s predatory response was also assessed by comparing Functional Responses. The results highlighted four key points: (1) increased temperature led to increased prey consumption in both females and males by decreasing handling time; (2) prey consumption was disproportionately higher in females than males, regardless of temperature; (3) temperature influenced females’ prey size selection; and (4) pregnancy reduced prey handling time among females. These findings show that temperature and intraspecific differences influence the feeding response of invasive fish, and they should both be taken into account when investigating and predicting the ecological impact of invasive species on invaded food webs.